Vegetation cover change and its response to human activities in the southwestern karst region of China - Liu, Zhaopu; Zhang, Yushan (Frontiers in Ecology and Evolution, 2024)
Vegetation to some extent can reflect the overall state of the ecological environment, and increasing vegetation cover can improve the quality of the ecological environment. The southwest karst region of China is a typical ecologically fragile area and an important ecological barrier. Against the backdrop of intensified human activities, the vegetation dynamics in the karst region have attracted widespread attention. Analyzing vegetation cover changes and their responses to human activities is important for regional ecological development. This study is based on SPOT-VGT NDVI data from 1998 to 2020 and employs trend analysis, "baseline" determination, multiple regression, residual analysis, and principal component analysis to investigate the characteristics of vegetation cover changes in the southwest karst region of China. Additionally, it quantifies the specific impacts of various human activities on these changes. The research findings indicate that (1) over the past 23 years, the interannual variability and seasonal differences in the NDVI of the southwest karst region have been significant, exhibiting an overall increasing trend. Spatially, the vegetation in this region demonstrates a decreasing trend from south to north and southwest to northeast. (2) Over time, the areas where vegetation has improved gradually expand, and the effectiveness of vegetation restoration increases with time. (3) Overall, human activities influence vegetation growth in the southwest karst landscape region of China. (4) The socioeconomic factors affecting vegetation cover changes in the southwest karst region of China primarily include economic development level, population and labor migration, urbanization development, and vegetation construction. These results provide a scientific basis for formulating reasonable ecological environment protection strategies by humans.